Effects of independent study and ability grouping on performance in english essay and letter writing among high-achieving students in Ibadan, Oyo State. (2015)
The study investigated effects of independent study and ability grouping on high-achieving students' performance in English essay and letter writing in Ibadan, Oyo State, using a pre-test, post-test, control group, quasi- experimental research design with a 3 x 2 x 2 factorial matrix. Six secondary schools and 78 SSS II high-achieving students were purposively selected as the participants were assigned into two experimental groups and control group. Students' Past Academic records, English Language Achievement Screening Test (r-0.72.), English Language Essay/Letter Achievement Test (r=0.78) and Academic Self-efficacy Scale (r-0.76) were the instruments used for the study. Participants in the experimental groups were instructionally facilitated and control group taught with the conventional method. Five hypotheses were formulated and tested at 0.05 significant level, while data analysed, using analysis of covariance (ANCOVA) and mean scores. Independent study and ability grouping were effective in improving the high-achieving students' performance in essay writing as the participants exposed to ability grouping had the highest mean score of 35. 934, followed by independent study with 32.478, showing better performance than their counterparts in the control group who had 25.879. The three groups maintained the same scoring order in letter writing performance, 33.405, 32.713 and 27.581. The result also revealed that in the two-way interaction effect of treatment and self-efficacy, there was a significant difference in high-achieving students' performance in essay writing (F(2.74) = 4.315, P < .05, η2 - .119), but no such interaction effect in their letter writing performance (F(2.74)) = .487, P > .05, η2=0.15). However, male and female participants in the experimental groups benefitted equally from the treatment packages. Based on these findings, teachers of English should use these educational strategies for high-achieving students' educational development